The potential impact of climate change on the genetic diversity of the endangered western leopard toad, Sclerophrys pantherina - Casola, Sarah (Percy FitzPatrick Institute of African Ornithology, 2017)
Climate change is now considered to be one of the greatest threats to the persistence of biodiversity. Much work has focused on the potential for climatic shifts to alter species' ranges, phenology, physiology, and behaviour, addressing higher level units of biodiversity from populations to biomes. However, the potential effects of climate change on the most fundamental unit of biodiversity, intraspecific genetic diversity, has only recently received research attention. Studies to date suggest that the accelerated climatic changes we currently face could cause a loss of intraspecific diversity, hampering the ability of populations to respond to further environmental change. Amphibians are considered to be one of the most vulnerable taxa to climate change. The amphibians of the Western Cape of South Africa provide a powerful opportunity to study the impact of climate change on genetic diversity, as many are endemic, threatened, and generally considered to be poor dispersers, limiting their ability to respond to climatic changes through range shifts. This project had two aims: first, to explore the potential impact of climatic shifts on the genetic landscape of the endemic and Endangered western leopard toad, Sclerophrys pantherina, a species with a disjunct distribution on either side of the Cape Flats. Second, I aimed to test the hypothesis that climatic fluctuations drive genetic divergence, a mechanism which may explain the potential overlap of high diversity areas with areas of high climatic instability. Population genetic analyses supported the findings of previous genetic work on S. pantherina, that populations in the Cape Metropole and the Overstrand Municipality (to the west and east of the Cape Flats, respectively) are genetically distinct, and thus should be treated as separate conservation units. Higher haplotype diversity was identified in the populations in the Cape Metropole when compared with the Overstrand, highlighting the importance of urban habitat patches in harbouring diversity in the species. Distinct pockets of low haplotype diversity were identified at Observatory and Hout Bay, suggesting a lack of connectivity between these and adjacent breeding sites, likely due to urban-associated habitat fragmentation. Species distribution modelling revealed that the species could lose a substantial amount of climatically suitable space in its current area of occurrence by 2070. Furthermore, the degree of loss was not uniform across the species' distribution. The populations of the Cape Metropole were predicted to experience greater losses in climatically suitable space than populations in the Overstrand. Additionally, the change in climatic suitability between the mid-Holocene (6,000 years ago) and present as well as the change in suitability between future (2050 and 2070) and present were significant predictors of genetic diversity, where areas of the greatest change in suitability between time periods were associated with the highest genetic diversity. Future efforts to conserve the species should focus on establishing connectivity between breeding sites to allow for the rescue of genetically depauperate sites. Efforts to mitigate the drastic negative effects of climate change predicted by the species distribution models should prioritise the breeding sites in the Cape Metropole, which are both higher in diversity and at greater risk from climate change. Mitigation efforts will likely require the application of engineered solutions to promote the maintenance of suitable wetland habitat for the species.